Getting the love you want: a guide for couples - Sandra van Wyk (AOSIS, 2000)
Dr Harville Hendrix is one of the world's leading marital therapists. He began his career as a therapist counselling both individuals and couples. He mentioned that he felt competent and effective with individuals, but saw the marital relationship as a complex system and he was not always capable of dealing with couples effectively. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.